Transplacental therapy of supraventricular tachycardia and hydrops fetalis in a twin pregnancy – case report and literature review - Carl M. Macalintal, Joseph; Castillo-Cheng, Maria Rosario; D. Cheng, Dexter Eugene (Prenatal Cardiology, 2021)
Fetal arrhythmias are rare, particularly in multifetal gestation. The most frequently reported fetal arrhythmias are premature atrial contractions and supraventricular tachycardia. Most of these conditions are benign and transient and do not require treatment. However, persistent fetal tachycardia, if left untreated, may lead to fetal hydrops, which is associated with high fetal mortality. Several studies have been performed regarding the success of transplacental anti-arrhythmic therapy in singleton pregnancies, but information on the management of multifetal gestation affected by fetal tachycardia is scarce. A 26-year-old gravida with twin pregnancy was diagnosed at 22 weeks of gestation with supraventricular tachycardia and hydrops in one of the fetuses. Transplacental anti-arrhythmic therapy using digoxin and amiodarone successfully achieved sustained cardioversion and resolution of the hydrops of the affected twin, with no documented maternal or fetal adverse effects. The resolution of fetal hydrops upon cardioversion confirms a cardiogenic cause of the condition. Antenatal fetal surveillance was performed based on the recommendations for monochorionic-diamniotic twin gestation. The pregnancy proceeded to term and was delivered by cesarean section due to malpresentation of the presenting twin. Normal cardiac findings of both twins were documented during postnatal evaluation.